Problems Encountered by Founding Principals During the Establishment Process of Public Schools and Proposed Solutions - Gökduman, Özgün; Gözler, Alpaslan (Fırat University, 2026)
This research was conducted to determine the problems faced by founding principals during the establishment phase of public schools affiliated to the Ministry of National Education and their suggestions for solutions to these problems. The research was conducted using case study design, one of the qualitative research techniques. The study group, which was formed to collect the research data, was determined using the criterion sampling method, which is one of the purposeful sampling methods. The opinions of 20 founding principals working in the establishment phase of public schools affiliated to MoNE in Kayseri province were consulted and the data were analyzed with descriptive analysis technique. According to the findings of the research, it was concluded that founding principals working in the establishment phase of public schools affiliated to MoNE in Turkey encountered many problems in bureaucratic procedures, physical structure of the buildings, producing economic solutions, meeting the needs of administrators, teachers and auxiliary staff, and that reducing the procedures they have reached for these problems, making school physical structure and budget planning by applying the opinions of experienced administrators, and meeting the needs of administrators, teachers and auxiliary staff with on-site solutions rather than temporary solutions affect the organizational culture and is not a task that is desired to be done. Keywords: Founding principal, public schools, solution suggestion

Bu araştırma; Milli Eğitim Bakanlığı’ na bağlı kamu okullarının kurulum aşamasında kurucu müdürlerin karşılaştıkları sorunları ve bu sorunlara çözüm önerilerini tespit amacıyla yapılmıştır. Araştırma, nitel araştırma tekniklerinden durum çalışması deseni kullanılarak yürütülmüştür. Araştırma verilerinin toplanması amacıyla oluşturulan çalışma grubu, amaçlı örnekleme yöntemlerinden olan ölçüt örneklem yöntemi kullanılarak belirlenmiştir. Kayseri ilinde bulunan MEB’ e bağlı kamu okullarının kurulum aşamasında görev yapan 20 kurucu müdürün görüşüne başvurulmuş ve veriler betimsel analiz tekniği ile analiz edilmiştir. Araştırma bulgularına göre Türkiye ‘de MEB’ e bağlı kamu okullarının kurulum aşamasında görev alan kurucu müdürlerin bürokratik işlemlerde, binaların fiziki yapısında, ekonomik açıdan çözümler üretme noktasında, yönetici, öğretmen ve yardımcı personel ihtiyacının giderilmesinde, birçok problemle karşılaştıkları ve bunlara yönelik ulaştıkları prosedürlerin azaltılması, deneyimli yöneticilerin görüşlerine başvurularak okul fiziki yapısının ve bütçe planlamasının yapılması, yönetici, öğretmen ve yardımcı personel ihtiyacının geçici çözümlerle değil yerinde çözümlerle yapılmasının kurum kültürünün etkilediği ve çokta yapılmak istenilen bir görev olmadığı sonuçlarına ulaşılmıştır. Anahtar Kelimler: Kurucu müdür, kamu okulları, çözüm önerisi
EĞİTİM KURUMLARININ KURULUM AŞAMASINDA KURUCU MÜDÜRLERİN KARŞILAŞTIKLARI SORUNLAR VE ÇÖZÜM ÖNERİLERİ
Keywords: Educational Psychology; Eğitim Psikolojisi